Initiated Chemical Vapor Deposition Kinetics of Poly(4-aminostyrene) - Khlyustova, Alexandra; Yang, Rong (Frontiers in Bioengineering and Biotechnology, 2021)
Initiated Chemical Vapor Deposition (iCVD) is a free-radical polymerization technique used to synthesize functional polymer thin films. In the context of drug delivery, the conformality of iCVD coatings and the variety of functional chemical moieties make them excellent materials for encapsulating pharmaceutics. Poly(4-aminostyrene) (PAS) belongs to a class of functionalizable materials, whose primary amine allows decoration of the delivery vehicles with biomolecules that enable targeted delivery or biocompatibility. Understanding kinetics of PAS polymerization in iCVD is crucial for such deployments because drug release kinetics in thin-film encapsulation have been shown to be determined by the film thickness. Nevertheless, the effects of deposition conditions on PAS growth kinetics have not been studied systematically. To bridge that knowledge gap, we report the kinetics of iCVD polymerization as a function of fractional saturation pressure of the monomer (i.e., Pm/Psat) in a dual-regime fashion, with quadratic dependence under low Pm/Psat and linear dependence under high Pm/Psat. We uncovered the critical Pm/Psat value of 0.2, around which the transition also occurs for many other iCVD monomers. Because existing theoretical models for the iCVD process cannot fully explain the dual-regime polymerization kinetics, we drew inspiration from solution-phase polymerization and proposed updated termination mechanisms that accounts for the transition between two regimes. The reported model builds upon existing iCVD theories and allows the synthesis of PAS thin films with precisely controlled growth rates, which has the potential to accelerate the deployment of iCVD PAS as a novel biomaterial in controlled and targeted drug delivery with designed pharmacokinetics.